Oleaceae endémicas del Perú - Sánchez, Isidoro (2006)
The Oleaceae are represented in Peru by six genera and 13 species (Brako & Zarucchi, 1993), mostly trees. Here we recognize two endemic species, in the same number of genera. These two endemic species are found in Desert Shrubland and Humid Lowland Amazonian Forests regions, between 250 and 1850 m elevation. Both endemic species have been recorded in the Peruvian System of Protected Natural Areas.